Effect of Bow and Stern Line Angle Variations on the Resistance of a 35,000 DWT Bulk Carrier Using CFD - HerawatyMagdalena Sihombing; Anggra Fiveriati; IGNA Satria Prasetya; Abdul Rohman (Indonesian Journal of Maritime Technology, 2026)
The shipping industry requires hull designs that can reduce hydrodynamic resistance and support energy-efficient vessel operation, particularly for bulk carriers with large displacement and relatively high-power demand. This study investigates the effect of bow and stern line angle variations on the total resistance of a 35,000 DWT bulk carrier using Computational Fluid Dynamics (CFD). The CFD results were also compared with the Holtrop method and Maxsurf Holtrop estimation to assess the consistency of the total resistance prediction trend. The principal dimensions used in the hull modelling were 178 m length between perpendiculars, 185.12 m waterline length, 29.7 m breadth, 14.8 m depth, 10.3 m draft, and a service speed of 16 knots. Three hull models were analysed: Model A as the initial hull configuration with 15.4° stern line angle and 23° bow line angle, Model B with a 1° increase in both the bow and stern line angles, and Model C with a 1° decrease in both line angles. The results show that, at 16 knots, Model C produced the lowest total resistance of 647.070 kN, compared with Model A at 655.434 kN and Model B at 670.372 kN. Compared with the initial hull configuration, Model C reduced the total resistance by 8.364 kN, equivalent to approximately 1.28%. The comparison among the Holtrop method, CFD simulation, and Maxsurf Holtrop estimation showed a similar increasing trend in total resistance with ship speed, with percentage differences of 7.76% between Holtrop and CFD and 5.28% between Maxsurf Holtrop and CFD at the operational speed. Therefore, among the three tested hull model variations, Model C demonstrated the most favourable resistance performance and may contribute to reducing the effective power requirement of the 35,000 DWT bulk carrier.